Korean approach to online protection for children in digital era - Abd Jalil, Juriah (2013)
Children are the most cherished members of our society but most vulnerable to harm, abuse, violence and exploitation in both online and offline world. The UN Convention on the Rights of the Child (UNCRC) prescribes the fundamental rights of children particularly to safeguard the liberty and protect the safety, security and privacy of the children. It imposed obligation on the state parties to protect the fundamental rights of children, which includes the right to life, survival and development; the right to be free and protected from harm, abuse, violence and exploitation; and the right to a fair trial and appropriate redress for children that have infringed or violated any law. These fundamental rights of the children particularly the right to be free from harm, abuse, violence and exploitation are being threatened with the existence of the internet and the digital technology.